(untitled) (Journal of Engineering, 2020)
The performance and durability of the asphalt pavement structure mainly depend on the strength of the bonding between the layers. Such a bond is achieved through the use of an adhesive material (tack coat) to bond the asphalt layers. The main objective of this study is to evaluate the effect of moisture in conjunction with repeated traffic loads on the strength of the bonding between asphalt layers using two types of tack coats with different application rates. Using the nominal maximum size of aggregate (NMAS), the layers were graded (25/19) and (19/9.5) mm. The slabs of multilayer asphalt concrete were prepared using a roller compactor using two types of tack coats to bond between layers, namely rapid curing cut back asphalt (RC-70) and cationic medium setting emulsion (CMS), with different application rates. Six extruded cores with a diameter of 116 mm each form the prepared slab has been obtained. Core specimens were subjected to moisture damage according to the American Association of State Highway and Transportation Officials (AASHTO), after which repeated bond shear stresses and monotonic tests are practiced. It is concluded that permanent deformation increased with moisture-induction under repeated load for both interfaces and tack coat types. The (CMS) as a tack coat had less permanent deformation values than RC-70 for both interface types and all application rates. In contrast, the interface bond strength (IBS) value was higher than that for (RC-70) in both interface types after moisture conditions. The trend of the results illustrates that (IBS) decreased with moisture conditions under repeated load, as compared to samples under repeated load only.